Association between Healthy Eating Index-2015 total and metabolic associated fatty liver disease in Americans: a cross-sectional study with U.S. National Health and Nutrition Examination Survey - Xu, Genzhong; Ma, Ermin; Zhang, Weitao; Feng, Bo (Frontiers in Nutrition, 2025)
BackgroundUtilizing the National Health and Nutrition Examination Survey (NHANES) dataset to investigate the relationship between dietary quality, as assessed by the Healthy Eating Index-2015 (HEI-2015), and the prevalence of metabolic associated fatty liver disease (MAFLD) among adults in the United States, our analysis revealed that an increased dietary quality was significantly correlated with a reduced risk of MAFLD in the American population.MethodThe NHANES dataset, encompassing the years 2017–2018 and comprising 3,557 participants, was incorporated into our analytical framework. Weighted multivariate linear regression model was performed to assess the linear relationship between the HEI-2015 and MAFLD. Dietary intake data were derived from two 24-h dietary recall interviews conducted as part of NHANES.ResultsFollowing multivariable adjustment, the weighted multivariable linear regression models demonstrated a negative correlation between the HEI-2015 total scores and the risk of MAFLD. The weighted logistic regression models revealed that each unit of increased HEI-2015 total value was associated with a 1.2% (95% CI: 0.9%, 1.5%; P < 0.001) decrease in the risk of f MAFLD. Upon categorization of the HEI-2015 scores into quartiles, the odds ratios (ORs) for the association between the risk of MAFLD and the quartile scores of HEI-2015, in comparison to the baseline quartile, were 0.945 (95% CI: 0.852–1.047; P = 0.279), 0.834 (95% CI: 0.750–0.927; P < 0.001), and 0.723 (95% CI: 0.646–0.811; P < 0.001), respectively. When participants were stratified by age and sex, subgroup analyses showed a similar trend. This pattern was also evident in the smooth curve fitting (SCF) and weighted generalized additive model (GAM).ConclusionElevated dietary quality, as assessed by the total and component food scores of the HEI-2015, was significantly correlated with a diminished risk of MAFLD among participants in the NHANES survey featured in this investigation.